2020
DOI: 10.1111/jeb.13611
|View full text |Cite
|
Sign up to set email alerts
|

Egg‐induced changes to sperm phenotypes shape patterns of multivariate selection on ejaculates

Abstract: Sperm cells exhibit extraordinary phenotypic diversity and rapid rates of evolution, yet the adaptive value of most sperm traits remains equivocal. Recent findings suggest that to understand how selection targets ejaculates, we must recognize that female‐imposed physiological conditions often alter sperm phenotypes. These phenotypic changes may influence the relationships among sperm traits and their association with fitness. Here, we show that chemical substances released by eggs (known to modify sperm physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 71 publications
(127 reference statements)
1
22
1
Order By: Relevance
“…We also calculated the proportion of motile sperm (PM) from the motile and total cell counts. These traits have previously been shown to be predictive of sperm success during both non-competitive and competitive fertilizations in M. galloprovincialis [50,53,57,58].…”
Section: (B) Experimental Overview and Temperature Treatmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…We also calculated the proportion of motile sperm (PM) from the motile and total cell counts. These traits have previously been shown to be predictive of sperm success during both non-competitive and competitive fertilizations in M. galloprovincialis [50,53,57,58].…”
Section: (B) Experimental Overview and Temperature Treatmentsmentioning
confidence: 95%
“…Sperm motility was measured immediately after temperature treatment by placing 2 µl of the sample onto an individual well of a 12-well multi-test slide, which had previously been washed with 1% polyvinyl alcohol to prevent sperm sticking to the slide. Elsewhere we have measured sperm motility both in seawater and in the presence of egg-derived substances that change swimming patterns [57]. Here, however, we confine the measures to seawater, as we would not have been able to separate the effects of high temperature treatments on the sperm themselves, from altered bioactivity of egg-derived substances.…”
Section: (B) Experimental Overview and Temperature Treatmentsmentioning
confidence: 99%
“…In these systems, it is relatively straightforward to collect spawned gametes from numerous individuals and conduct biologically relevant fertilization assays in the laboratory. Indeed, several recent studies have examined natural selection on broadcast spawner ejaculates using non-competitive fertilization trials, and these have reported complex patters of linear and nonlinear selection on combinations of sperm traits [80][81][82][83][84].…”
Section: Selection On Ejaculatesmentioning
confidence: 99%
“…The role of female reproductive fluids in chemotaxis to lead specific sperm cohorts to the eggs has been described first in broadcast-spawning marine invertebrates [32], but different forms of chemotaxis are also found in other taxa including fishes [33][34][35] and internal fertilizers such as mammals [36]. Female reproductive fluid composition varies among individuals [37,38], and can affect sperm motility and velocity as well as fertilization dynamics [39][40][41]. The composition of the female reproductive fluid may be influenced by female condition [42], and is, therefore, likely to be similarly influenced by other environmental factors, with consequences for fertilization success and offspring fitness.…”
Section: Environmental Effects On Gamete Phenotypesmentioning
confidence: 99%